VIRAL LOAD AND OPPORTUNISTIC INFECTION AS THE INDICATOR OF QUALITY-OF-LIFE PEOPLE WITH HIV/AIDS - Yuliaty, Rina; Rusli, Adria; Rohman; Rayasari, Fitrian; Kurniasih, Dian Noviati; Aini, Nur; Shahroh, Yuni; Maemun, Siti; Saadulloh, Dadang; Yunitri, Ninik (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Human immunodeficiency virus (HIV) is a significant concern in the field of global health. However, studies on the relationship between viral load, opportunistic infections, and quality-of-life among them are limited. Objectives: This study aims to determine the relationship between viral load count, the presence of opportunistic infection, and the quality-of-life among people living with HIV. Methods: A cross-sectional study was used involving 35 respondents recruited through convenience sampling. The quality-of-life of individuals living with HIV was assessed using the World Health Organization Quality-of-Life instrument for HIV. Statistical analysis using descriptive statistics, including mean, standard deviation, and proportion, and bivariate analysis with p-value<0.05. Results: Of the 35 participants, the majority were male (57.1%), with a mean age of 41.63 (9.09), and had a low education level (51.4%). The mean quality-of-life score was 86.88 (12.27), with a mean duration of ARV treatment of 7.23 years (5.36), undetectable viral load (68.6%), living with opportunistic infections (80%), and with tuberculosis being the most common (52.63%). There was a significant correlation between viral load and overall quality-of-life (p-value 0.04). Conclusion: The results of viral load testing and the identification of opportunistic infections can serve as indicators to assess the quality-of-life among people living with HIV. The outcomes of this study have practical implications for enhancing healthcare services in clinical settings. This information can guide the implementation of targeted interventions to strengthen social relationships and these individuals' environmental quality-of-life.